Workshop in Fiqh Muamalat in Medicine 2013: venturing further collaboration between Kulliyyahs of Medicine and lslamic Revealed Knowledge, IIUM. - Sharifudin, Mohd Ariff; Mohd Yusof, Nazri; Wan Husin, Wan Rumaizi; Che Ahmad, Aminudin; Khan, Ed Simor; Awang, Mohd Shukrimi (2013)
Fiqh Muamalat in Medicine 2013 is the third of a series of workshop that has been conducted with the aim of producing holistic medical practitioners by International Islamic University Malaysia (IIUM) The workshop aimed to incorporate fiqh muamalat in the teaching and practice of medicine. It was run over two days with a series of lectures and case discussions. Lectures included "Introduction to Fiqh Muamalat", "Takaful and Insurance", "Munakahat", "Faraidh" and "Medical Professionalism". Various case scenarios related to the topics discussed were debated and explored. The workshop was also opened to academic staff, hospital staff, other postgraduate students, as well as interested undergraduate students. At the end of the workshop, feedback forms were distributed and responses were evaluated. The feedback solicited participants' ratings on various aspects of the workshop. In an open-ended section participants were asked to describe the most important thing they learnt from the workshop as well as the most important thing that can be improved. Forty one participants responded. The evaluation showed that the majority of participants rated it as good (68.3%), and interested to receive further information on future workshops or seminars. Some participants would like certain topics to be elaborated in depth which included issues on illegitimate child, terminally ill patients, and inheritance. Among the suggestions to improve future workshops include better promotion of event, more case scenarios, group activities and a longer duration of the workshop. Overall, the workshop was a well-accepted and useful program perceived by participating students and lecturers. Collaborative work between Kulliyyah of Medicine and Kulliyyah of Islamic Revealed Knowledge are important in producing holistic medical practitioners especially from IIUM.